TANGGUNG GUGAT MASKAPAI PENERBANGAN TERKAIT BATALNYA PENERBANGAN AKIBAT PANDEMI COVID-19 - Nataliayana, Theresia Priska (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The research entitled Airline Liability Related to Flight Cancellations Due to the Covid-19 Pandemic aims first to find out the form of airline liability related to flight cancellations due to the Covid-19 Pandemic. The second is to determine the suitability of the implementation of the Refund Ticket against the Minister of Transportation Regulation Number PM 25 of 2020. The research method used in this thesis is a normative legal research method, namely by examining the norms and principles that apply to positive law, as well as research that examine document studies, namely using various secondary data such as laws and regulations, court decisions, legal theory, and can be in the form of opinions of scholars, not only that this type of normative research uses qualitative analysis. From the research results it can be concluded First: that the form of airline liability related to flight cancellations due to the Covid-19 Pandemic is regulated in the Minister of Transportation Regulation of the Republic of Indonesia Number PM 25 of 2020. Which in the Minister of Transportation Regulation regulates flights that are canceled due to the Covid-19 Pandemic, the responsibility Airline claim is in the form of a full or 100% refund of ticket costs to prospective passengers whose tickets have been canceled on the dates specified in the Minister of Transportation Regulation. Second: the implementation of ticket refunds in other Minister of Transportation Regulations is in the form of refunding ticket fees in accordance with the provisions. Furthermore, the conformity of the refund ticket implementation in the Minister of Transportation Regulation No. PM 25 of 2020 stipulates that the form is in the form of a coupon or voucher.